Development of electronic media on food preservation - An effective tool for information dissemination - Goswami, Gitasree; Mohapatra, Sanghamitra; Singh, Anita (Indian Journal of Hill Farming, 2019)
Electronic Media is the heart of modern culture and edutainment. In todayâ€™s world, mediaÂ has played an important role in raising our society. Considering the important role playedÂ by the electronic media, a research study entitled â€œDevelopment of electronic media onÂ food preservation - An effective tool for information dissemination.â€ was undertaken withÂ the objectives to find out the effectiveness of electronic media for informationÂ dissemination. A close ended evaluation schedule was prepared to evaluate the developedÂ compact disc (CD) as an electronic media. Sixty respondents were selected purposively forthe evaluation of the developed compact disc. The main objective of the CD was fulfilledÂ as all the three respective groups gained the required information of importance and needÂ through the CD on food preservation. As a result, it can be concluded from the study thatÂ the CD on food preservation had shown positive result for the villagers. CD has played aÂ major role in education of illiterate and semi-literate rural population as an effectiveÂ electronic media.